2014
DOI: 10.1371/journal.pone.0114461
|View full text |Cite
|
Sign up to set email alerts
|

Inference of the Oxidative Stress Network in Anopheles stephensi upon Plasmodium Infection

Abstract: Ookinete invasion of Anopheles midgut is a critical step for malaria transmission; the parasite numbers drop drastically and practically reach a minimum during the parasite's whole life cycle. At this stage, the parasite as well as the vector undergoes immense oxidative stress. Thereafter, the vector undergoes oxidative stress at different time points as the parasite invades its tissues during the parasite development. The present study was undertaken to reconstruct the network of differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…allosamidin) were shown to decrease oocyst numbers (Shahabuddin et al, 1993;Shahabuddin and Kaslow, 1994a,b;Zieler et al, 1999;. Humoral insect defence mechanisms however remain potent inhibitors when the ookinete crosses the epithelial layer (James, 1928;Dimopoulos, 2003;Osta et al, 2004;Christophides, 2005;Povelones et al, 2011;Shrinet et al, 2014).…”
Section: Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…allosamidin) were shown to decrease oocyst numbers (Shahabuddin et al, 1993;Shahabuddin and Kaslow, 1994a,b;Zieler et al, 1999;. Humoral insect defence mechanisms however remain potent inhibitors when the ookinete crosses the epithelial layer (James, 1928;Dimopoulos, 2003;Osta et al, 2004;Christophides, 2005;Povelones et al, 2011;Shrinet et al, 2014).…”
Section: Fertilizationmentioning
confidence: 99%
“…Recognizing the female gametocyte provides the majority of the biomass of the zygote/ookinete, this expansion of energy provision is understandable, but the male gametocyte forms eight microgametes devoid of both plastids, suggesting in the male cell that it performs a vital function during gametocytogenesis or during the dramatic events of gamete formation in the mosquito? It has been shown that the apicoplast provides isoprenoids essential for gametocytogenesis (Wiley et al ., ), and up‐regulation of glyoxalase provides defence against oxidative stress (Okamoto et al ., ) that has recently been shown to be a component of the mosquitoes' responses to malarial infection (Shrinet et al ., ). Up‐regulation of genes encoding type II fatty acid, and 15 of 16 TCA enzymes in the mature gametocyte are also consistent with the cytological observations.…”
Section: Introductionmentioning
confidence: 97%
“…This data was correlated with expression levels of 9255 mRNA transcripts of An. stephensi generated using same midgut samples [ 34 ]. Transcripts showing both negative and positive correlation with miRNAs and threshold cut off of 0.9 were selected for further analysis ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fold change in miRNA expression profile deduced by real time PCR was used for co-expression analysis. For mRNA expression data, we obtained RNA-Seq data generated using midgut tissues of sugar fed naive female mosquitoes 6–8 days old (SF), female mosquitoes at 5 days post blood-feeding (BF 5d), 5 days post Plasmodium vinckei petteri infected blood feeding (iBF 5d) and 5 days post human blood-fed (HBF 5d) mosquitoes [ 34 ]. Data were normalized (FPKM values calculated) and fold change of transcripts were calculated using SF as a calibrator.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size (n=376) was very small to deduce meaningful classifications and the author concluded that more work would be needed [27]. Despite this, there have been far reaching studies on application of ML in other areas of malaria research [28][29][30][31][32]. The diagnosis of malaria using ML on clinical datasets has been impaired by lack of large data, as well as difficulty in data curation.…”
mentioning
confidence: 99%